THE EFFECT OF INCENTIVES, WORK MOTIVATION, AND WORK STRESS ON THE PERFORMANCE OF GRABBIKE DRIVERS IN BEKASI - Edward Efendi Silalahi; Rohman Nul Karim; Tyna Yunita (Draf Solusi Indonesia, 2023)
This study aims to determine whether incentives, work motivation, and work stress affect the performance of grabbike drivers in Bekasi. This research is a quantitative research with grabbike drivers as subjects and objects in Bekasi. The sampling technique used accidental sampling with a total sample of 90 respondents. using the SPSS 22 statistical tool. The results of this study provide an explanation that the incentive variable has a positive effect on the performance of grabbike drivers, work motivation has a positive effect on the performance of grabbike drivers and work stress has a negative effect on the performance of grabbike drivers. Then simultaneously the variables of incentives, work motivation, and work stress affect the performance of grabbike drivers.